IMPLEMENTASI SHARED CHRISTIAN PRAXIS SEBAGAI SOLUSI UNTUK MENGATASI FENOMENA BULLYING DI SEKOLAH - meilanialow9; Fibby Pricilia Punu; Tesalonika Kambey; Iren Ransulangi; Avril Rompis; Tesalonika Mongilala; Treisya Kasukung; Exel Tamba (PT. Giat Konseling Nusantara, 2026)
Bullying has become a prevalent issue in schools and is often perceived as normal, resulting in detrimental impacts on students' psychological development and social relationships. This study employs a literature review method to examine Thomas Groome’s concept of Shared Christian Praxis (SCP) as an educational approach to address this problem. The purpose of this paper is to explain how SCP can be implemented within the school context to prevent and manage bullying. The findings indicate that shared christian praxis (SCP) through reflection on experience, critical reflection, Christian story and vision, dialectical hermeneutics, and the vision emerging from the Christian story can be utilized to shape students' moral consciousness and foster a school culture of mutual respect, free from bullying.